Códigos de grupo sobre grupos não abelianos. - Souza, Emanoel Ferreira de (2018)
Let G be a finite group and F a field. We show that all G-codes over F are abelian if the order of G is less than 24, but for F = Z5 and G = S4 there exist non-abelian G-codes over F, answering to an open problem posed in BERNAL, J. J, DEL RÍO, A, and SIMÓN, J. J (2009). This problem is related to the decomposability of a group as the product of two abelian subgroups. We consider this problem in the case of p-groups, finding the minimal order for which all p-groups of such order are decomposable. Finally, we study if the fact that all G-codes are abelian remains true when the base field is changed.